Microbiota Features Associated With a High-Fat/Low-Fiber Diet in Healthy Adults - Bailén, María; Bressa, Carlo; Martínez-López, Sara; González-Soltero, Rocío; Montalvo Lominchar, Maria Gregoria; San Juan, Celia; Larrosa, Mar (Frontiers in Nutrition, 2020)
The intake of saturated fatty acids (SFA) is related to the onset of obesity, inflammation and cancer related diseases, and only when it is replaced by the intake of unsaturated fat and unrefined carbohydrates is the promotion of those disorders attenuated. Gut microbiota has emerged as a new factor that could be involved in the development of these disorders, and it is also one of the factors most influenced by the host diet. The goal of our study was to determine whether the gut microbiota of healthy individuals whose intake of SFA exceeds WHO recommendations presents specific features similar to those reported in people with obesity, inflammation, cancer or metabolic diseases. 109 healthy non-obese subjects were enrolled in the study and divided into two groups according to their SFA intake. Body composition and gut microbiota composition were analyzed, and associations between bacterial taxa, diet and body fat composition were determined globally and separated by sex. Metagenome functional pathways were predicted by PICRUSt analysis. Subjects whose SFA intake exceeds WHO recommendations also presented a dietary pattern associated with a lower fiber intake. This high saturated fat and low fiber diet was associated with a greater abundance of the Anaerotruncus genus, a butyrate producer associated with obesity. When data were analyzed by sex, the women in the HSFA group presented a greater abundance of Campylobacter, Blautia, Flavonifractor and Erysipelatoclostridium. The HSFA men showed higher levels of Anaerotruncus, Eisenbergiella, FamilyXIIIUCG_001 and two genera from the Lachnospiraceae family. The PICRUSt analysis was in accordance with these data, showing correlation with a decrease in the cofactor levels of some metals such as iron, needed to maintain a healthy metabolism. Our study shows that the microbiota of healthy people with a high SFA diet contains bacterial taxa that could be related to the development of some diseases, especially obesity and other pro-inflammatory diseases in women. Differences in gut microbiota according to sex suggest that women and men could differentially benefit from following a specific diet. Our study identifies bacterial taxa that could be considered as early predictors for the onset of different diseases in healthy subjects.